A review of the genus Gyrophaena Mannerheim 1830 (Coleoptera: Staphylinidae: Aleocharinae: Gyrophaenina) of the Caucasus and adjacent territories - Enushchenko, Ilya V.; Semenov, Viktor B. (Zootaxa, 2016)
A review of the genus Gyrophaena Mannerheim 1830 of the Caucasus and adjacent territories, with faunistic data for twenty three species is provided. G. (Phaenogyra) atropatena Enushchenko, sp. nov. of Azerbaijan and Iran is described and illustrated. One new synonymy is established: G. (s.str.) caucasica A. Strand 1939 = G. (s.str.) cultellata Assing 2009, syn. nov. G. (s.str.) orientalis A. Strand 1938 and G. (s.str.) poweri Crotch 1867 are reported for Caucasus for the first time. Records of G. (s.str.) congrua Erichson 1837, G. (s.str.) joyioides Wüsthoff 1937, and G. (s.str.) pulchella Heer 1839 for Caucasus are not confirmed by new material. G. (s.str.) caucasica is recorded for the Republic of Crimea and Rostov Area of Russia for the first time. Additional new Palaearctic records for some species are provided. An illustrated key for all studied species of Caucasus is given.